XPC: fast and reliable synchronous transmission protocols for 2-phase commit and 3-phase commit - Spina,A; Breza,M; Dulay,N; McCann,J (ACM, 2020)
The improvement of software abstractions and frame-works for programmers is one of the major challenges forthe engineering of reliable and efficient wireless sensing sys-tems. We address this challenge with X Process Commit(XPC), an atomic commit protocol framework, andHybrid,a Synchronous Transmission (ST) communication approach.Hybridexploits the reliability of Glossy and the speed ofChaos, two Synchronous Transmission primitives, to getlower latency and higher reliability than either on their own.Hybridis a general approach that can provide reliable com-munication for any round based protocol. We use XPC andHybridto build the classical 2-phase and 3-phase commitprotocols. Through extensive experimentation, we comparethe performance of the 2-phase and 3-phase commit proto-cols when they useHybrid, Glossy, and Chaos for commu-nication. Our results show thatHybridis more robust thanChaos to radio interference, with almost 100% reliability in anetwork of nodes suffering from moderate radio interference,13% to 50% faster than Glossy, and has comparable over-heads to other state of the art ST atomic commit approachesA2/Synchrotron.